Upconversion nanocomposites for photo-based cancer theranostics. Issue 32 (14th July 2016) - Wang, Shuailiang; Bi, Anyao; Zeng, Wenbin; Cheng, Zhen
Abstract : Upconversion nanoparticles (UCNPs) are able to convert long wavelength excitation light into high energy ultraviolet (UV) or visible emissions, and they have attracted significant attention because of their distinct photochemical properties including sharp emission bands, low autofluorescence, high tissue penetration depth and minimal photodamage to tissues. Abstract : Lanthanide ion doped upconversion nanoparticles (UCNPs) are known to be able to convert long-wavelength excitation light (usually 980 nm) into high-energy ultraviolet (UV) or visible emissions, and they have attracted significant attention because of their distinct photochemical properties including sharp emission bands, low autofluorescence, high tissue penetration depth, inertness to ambient interference and minimal photodamage to tissues. Until now, UCNPs have shown great potential in various realms including bioimaging, biosensing and biomedical applications. Especially in recent years, UCNP based nanocomposites have been found to be promising tools for multi-modal imaging and low-invasive photo-based therapy of tumors. In this review, we summarize the recent achievement and progress of UCNP based multifunctional nanoplatforms for bioimaging and cancer phototheranostics, including photodynamic therapy (PDT) and photothermal therapy (PTT). Furthermore, some emerging trends, future directions as well as challenges in this rapidly growing field are discussed.